Epicardial adipose tissue in patients with and without COVID-19 infection - Alexander J. Küng; Iryna Dykun; Matthias Totzeck; Raluca Mincu; Lars Michel; Clemens Kill; Oliver Witzke; Jan Buer; Tienush Rassaf; Amir A. Mahabadi (American Heart Journal Plus)
Background: Acute COVID-19 infection frequently affects the cardiovascular system and causes acute myocardial injury. Epicardial Adipose Tissue (EAT), a visceral adipose tissue surrounding the myocardium and coronary arteries, has unique paracrine and endocrine effects, modulating the heart's inflammatory environment. Systemic inflammation stimulates TNF-α and Interleukin-6 secretion from EAT, contributing to cytokine storms and intensifying systemic responses. We aimed to determine whether EAT amount differs in patients with and without acute COVID-19 infection and myocardial injury. Methods: This study analyzed the CoV-COR registry cohort, conducted at the University Hospital Essen, including patients with symptoms suggestive of COVID-19 infection. The infection was confirmed by PCR. EAT thickness was measured by two-dimensional TTE. Results: A total of 296 patients (mean age 63.6 ± 17.26 years, 55.4 % male) were included. Patients with confirmed COVID-19 infection were younger, more frequently treated with antihypertensive medication, and had higher BMI and systolic blood pressures. Univariate logistic regression showed no association between EAT and myocardial injury 0.97 (0.74; 1.28, p = 0.82). A trend towards an association was observed between increasing EAT thickness and COVID-19 infection 1.25 (0.99; 1.59, p = 0.060). Adjusting for age and gender strengthened the association, with a 48 % (1.14; 1.93, p = 0.004) increased odds of COVID-19 infection per increase in EAT thickness. Multivariable regression yielded consistent effect sizes 1.47 (1.01; 2.16, p = 0.047). Conclusion: EAT thickness is associated with the presence of an acute COVID-19 infection but not with a myocardial injury. Further research is needed to assess if systemic viral infection induces dynamic changes in EAT.